Linear Multistep Method for Advanced IDEs with Piecewise Constant Arguments. (23rd April 2022) - Mei, Liangcai; Wu, Boying; Lin, Yingzhen
Abstract : In this article, based on the linear multistep method, we combined the simplified reproducing kernel method (SRKM) with the optimization method to solve advanced IDEs with piecewise constant arguments. This article also discussed the convergence order and the time complexity of the method. It is proved that the approximate solutions and their derivatives obtained by this algorithm are uniformly convergent. Through two numerical examples, it is proved that the proposed algorithm is obviously better than other methods.